Determination of Trace Elements and Rare Earth Elements in Gannan Navel Orange Fruit by ICP-MS - Cai, Dingjian; Rui, Yukui (Asian Journal of Chemistry, 2012)
Gannan navel orange is a famous brand in China, but mineral element content in Gannan navel orange is not systematically studied. In present work, eight trace elements in Gannan navel orange from Jiangxi province were determined by ICP-MS. The results showed that Navel orange fruits contained many kinds of mineral elements, especially Mn, Fe and B, which should be the causes that Gannan navel orange is delicious and has a good taste.